Indeterminacy and structure of the off camera: Analítica del fuera de campo y su carácter constitutivo de la obra - Sánchez Domínguez, Antonio; Juárez López, Jorge (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A The offscreen (off camera or offstage) constitutes one of the main formal elements of cinema. Its centrality in the process of creation and in how it produces cinematic performances does not find enough intellectual interest in academic analyses, often more focused on “what appears on screen” than on what “does not appear”. This investigation aims to show this centrality in the shadow, this centrality of “what does not appear in the screen”, its radical importance and even its capacity to completely rewrite what de facto appears in the image. This would even lead to blurring the ontological entity of “what appears”, leading to the fact that what appears is precisely what was originally off camera.